Using I-Hubs for Bridging The Gap of Digital Divide in Rural Kenya - Lusweti, Samuel; Omieno, Kelvin (Information System; Universitas Buana Perjuangan Karawang, 2023)
The world is moving towards digital economy where almost everything being done today is digitally controlled because necessity is the mother of innovation. Everybody is striving to attain digital stability as a lot of revenue is generated in the digital world. Digital divide therefore becomes so disadvantageous to people left without access to computers and the internet. In this paper, researchers discuss the role of Kenyan innovation hubs in closing the gap between those who have access to the internet and computers and those who do not. The paper discuss the World Bank projection of the GDP emanating from the use of ICTs and the challenges facing innovation. Government support plays a key role in ensuring that the people secluded from ICTs are able to access these services especially those in rural areas. This research found that in Kenya, innovation hubs have helped the citizens staying in rural areas to gain access to internet and develop their ideas and innovations as well as undergo mentorship. Nonetheless, a lot of support is needed from the Kenyan government through the launching of more innovation hubs especially in rural areas that can help improve the online business, innovation and thus increase the GDP from ICTs.